2011
DOI: 10.1002/cpp.795
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cognitive–Behavioural Therapy Plus Pharmacotherapy in Inpatient Treatment of Depressive Disorders

Abstract: There is a need for treatment strategies to accompany medication. In the Sequenced Treatment Alternatives to Relieve Depression trial (STAR*D), only 33% of the patients reached remission criteria after the first antidepressant treatment step and only 50% after the second step. The strict inclusion criteria of randomized controlled trials often render their patient populations unrepresented. For an accurate view of treatment effectiveness, their results need to be complemented with results gained from trials in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 31 publications
0
18
0
3
Order By: Relevance
“…As with non-CD patients, additional psychotherapy resulted in improved treatment regarding depressive symptom scores, compared with patients who received pharmacotherapy only (Cuijpers et al, 2009). This could also be shown for depressive inpatients (Köhler et al, 2013a). CD patients show higher comorbidities and non-response rates to pharmacology and psychotherapy.…”
Section: Pharmacotherapymentioning
confidence: 93%
“…As with non-CD patients, additional psychotherapy resulted in improved treatment regarding depressive symptom scores, compared with patients who received pharmacotherapy only (Cuijpers et al, 2009). This could also be shown for depressive inpatients (Köhler et al, 2013a). CD patients show higher comorbidities and non-response rates to pharmacology and psychotherapy.…”
Section: Pharmacotherapymentioning
confidence: 93%
“…For example, Kohler et al . () found reductions in symptoms for service users with unipolar depression, who had received twice‐weekly CBT for an average of 13 sessions. Similarly, Schramm et al .…”
Section: Introductionmentioning
confidence: 99%
“…A small body of evidence indicates that individual psychological therapy in inpatient settings can be effective. For example, Kohler et al (2013) found reductions in symptoms for service users with unipolar depression, who had received twice-weekly CBT for an average of 13 sessions. Similarly, Schramm et al (2007) found improvements in service users with major depression, who had received interpersonal therapy for 15 sessions, three times a week.…”
mentioning
confidence: 99%
“…Despite the heated debate regarding the superiority of one treatment over others, there is fairly wide acceptance of the 'Dodo Bird Verdict ' (Luborsky et al 1975), at least in the case of depression, suggesting that all treatments are more or less equally effective (Cuijpers et al 2008;Barth et al 2013). Furthermore, research in the past two decades has taught us that psychotherapeutic treatments of depression are superior to waitlist and other control conditions (Barth et al 2013;Lambert, 2013), and that psychotherapy combined with anti-depressant medication is more effective than medication alone (Barber et al 2013;Köhler et al 2013;Hollon et al 2014;Fonagy, 2015;Leichsenring et al 2015). There is also evidence suggesting that some types of psychotherapies are not only as effective as medication, but also have higher long-term enduring effects (Hollon & Ponniah, 2010;Cuijpers et al 2013b).…”
Section: What Do We Know About the Efficacy Of Psychotherapies For Dementioning
confidence: 99%
“…Robust evidence supports its superiority over control conditions (DeRubeis et al 2005;Tolin, 2010;Cuijpers et al 2013a;Marcus et al 2014), and some studies found that combined treatment is superior to medication alone (Cuijpers et al 2013a;Köhler et al 2013;Hollon et al 2014). When comparing CBT to alternative treatments, there are mixed findings (Hofmann et al 2012).…”
Section: Cognitive-behavioral Therapy (Cbt)mentioning
confidence: 99%